Studies and Essays: The Inn of Tranquility, and Others - Galsworthy, John, 1867-1933 (Salt Lake City, UT : Project Gutenberg, 2004)
"Studies and Essays: The Inn of Tranquility, and Others" by John Galsworthy is a collection of essays written in the early 20th century. This book presents a range of reflections on life, society, and human nature, with each essay exploring different themes and ideas that echo the complexities of existence. Galsworthy$1 (Bs writing is imbued with a philosophical depth, aiming to provide insights into contemporary issues while maintaining a poetic quality. In this collection, Galsworthy traverses various topics, from the simplicity of rural life depicted in "The Inn of Tranquility" to the existential nuances explored in "A Christian." Each essay features vivid imagery and contemplative narratives, often centered around his observations of people and nature. For instance, "The Black Godmother" examines the consequences of fear and misunderstanding through a poignant story about a mistreated dog. Galsworthy employs these narratives to delve into broader social issues, overcome by a sense of empathy and a critical view of societal norms. The essays resonate with emotional truth, inviting readers to reflect on the delicate balance between human experience and the natural world. (This is an automatically generated summary.)s
The Inn of Tranquillity -- Magpie over the hill -- Sheep-shearing -- Evolution -- Riding in mist -- The procession -- A Christian -- Wind in the rocks -- My distant relative -- The black godmother.
Release date is 2004-09-24
Produced by David Widger
Keywords: Essays; Short stories; Autobiographical fiction